Microcos kinabaluensis - Tsen, S.; Mohd Yusof, Nur Adillah, M.Y.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Microcos kinabaluensis is a tree, endemic to Sabah. Due to land use change, it is suspected that the population declined by at least 80% (based on reduction analysis in GeoCAT). Habitat loss has been caused by agricultural and ecotourism development over the last three generations of the species. There is no recent collection for this species. The remaining estimated area of occupancy (AOO) and extent of occurrence (EOO) are both 8 km2, although with greater collection effort these may be larger. The species remains in a protected area, and threats are not considered to be continuing. This tree is assessed as Critically Endangered. Microcos kinabaluensis is endemic to Sabah, Malaysia. It is known from Mount Kinabalu and vicinity.